Chromogenic Photonic Crystal Sensors Enabled by Multistimuli‐Responsive Shape Memory Polymers. Issue 12 (31st January 2018) - Leo, Sin‐Yen; Zhang, Wei; Zhang, Yifan; Ni, Yongliang; Jiang, Helena; Jones, Cory; Jiang, Peng; Basile, Vito; Taylor, Curtis
Abstract: Here novel chromogenic photonic crystal sensors based on smart shape memory polymers (SMPs) comprising polyester/polyether‐based urethane acrylates blended with tripropylene glycol diacrylate are reported, which exhibit nontraditional all‐room‐temperature shape memory (SM) effects. Stepwise recovery of the collapsed macropores with 350 nm diameter created by a "cold" programming process leads to easily perceived color changes that can be correlated with the concentrations of swelling analytes in complex, multicomponent nonswelling mixtures. High sensitivity (as low as 10 ppm) and unprecedented measurement range (from 10 ppm to 30 vol%) for analyzing ethanol in octane and gasoline have been demonstrated by leveraging colorimetric sensing in both liquid and gas phases. Proof‐of‐concept tests for specifically detecting ethanol in consumer medical and healthcare products have also been demonstrated. These sensors are inexpensive, reusable, durable, and readily deployable with mobile platforms for quantitative analysis. Additionally, theoretical modeling of solvent diffusion in macroporous SMPs provides fundamental insights into the mechanisms of nanoscopic SM recovery, which is a topic that has received little examination. These novel sensors are of great technological importance in a wide spectrum of applications ranging from environmental monitoring and workplace hazard identification to threat detection and process/product control in chemical, petroleum, and pharmaceutical industries. Abstract : Novel chromogenic photonic crystal sensors, which exhibit easily perceived color changes in response to different analyte concentrations, are enabled by multistimuli‐responsive shape memory polymers possessing nontraditional all‐room‐temperature shape memory effects. These sensors with high sensitivity, specificity, and unprecendented measurement range are inexpensive, reusable, durable, small footprint, and are deployable with mobile platforms for low‐cost quantitative analysis.